Design of direct wave cancellation system for high‐frequency CW radar. Issue 20 (15th August 2019) - Shang, Nan; Xin, Ke; Yu, Changjun; Wang, Linwei
Abstract : When high‐frequency continuous wave (HFCW) radars transmit linear frequency modulated (LFM) continuous wave, there will be direct wave (DW) interference due to temporal continuity. In order to prevent receiver saturation, a DW cancellation system device is developed. This study studies the theoretical model of RF cancellation and derives the DW cancellation ratio formula. Afterwards, a system design scheme for DW cancellation is proposed, where the design and system control algorithms of each module of the cancellation system are mainly studied. Finally, by analysing the DW cancellation technique under multipath effect, it is found that the multipath effect will affect the depth of cancellation. The simulation results verify the correctness of the system design method, the measurement shows a leakage suppression of >15 dB under multipath effects.